SCIENTIFIC PERSPECTIVES ON ENHANCING THE PRACTICE OF ENTERPRISE LENDING ON THE BASIS OF INNOVATIONS - Khasanov Shamsiddin Khafizovich (World Scientific Research Journal, 2025)
Abstract.This article examines the issues of improving the practice of lending to manufacturing enterprises on the basis of innovations. Within the framework of the study, the theoretical role of lending in ensuring economic growth and sustainability is substantiated. The impact of modern financial instruments, digital technologies, and fintech solutions on credit operations is analyzed. International experience and standards are comparatively studied, highlighting opportunities for their integration into the national system. The efficiency of credit resources for manufacturing enterprises and their significance in enhancing investment potential are revealed. In addition, advanced methods of credit risk management are explored. The article relies on economic literature and the results of foreign research. The ways of achieving competitiveness through the introduction of an innovative credit policy in the national banking system are justified. The scientific conclusions of the research are aimed at solving practical problems. Thus, the role of innovations in ensuring the efficiency and sustainability of lending practices for manufacturing enterprises is emphasized